Impulsive Buying of Fashion Goods on Digital Marketplace among Z-Generation in Batam City: a Multi Method Analysis Approach - Aripradono, Heru Wijayanto; Silvina, Silvina (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to determine factors such as ideal self-congruence, fashion consciousness, positive emotion, materialism, product attributes, online platform quality, and online sales promotion that affect impulsive buying behavior among Z-Generation in Batam. This study uses quantitative and qualitative method. Sampling method used is convenience sampling for quantitative and disproportionate stratified sampling for qualitative data. A total of 400 questionnaire respondents and 20 interviews which target specifically had an experience of buying fashion products through online platforms, generation Z, and live in Batam. Data analysis using regression analysis by SPSS Statistics 26. The result shows that fashion consciousness, materialism, product attributes, and online sales promotion have a significant effect on impulsive buying. This study provides a different demography compared to previous research, as people from different ages, places, and culture may behave in a different way considering their lifestyle. These can provide insight into what should attract impulsive buying behavior towards Z-Generation consumers in Batam.